Scar contracture prevention with local steroid injections in transoral videolaryngoscopic surgery. Issue 5 (October 2020) - Uno, Kosuke; Tomifuji, Masayuki; Araki, Koji; Tanaka, Shingo; Taniai, Shinichi; Tanaka, Yuya; Kimura, Eiko; Ogawa, Kaoru; Shiotani, Akihiro
Abstract: Objective: The aim of this study was to evaluate the efficacy and safety of local steroid injections to prevent scar contracture after transoral videolaryngoscopic surgery (TOVS) in hypopharyngeal cancer patients. Methods: Patients were enrolled in this study if they had received a local steroid injection during TOVS and had attended an outpatient clinic after at least three months. All patients were being treated for hypopharyngeal cancer and received a single session of triamcinolone acetonide, injected using a 21-gage needle. Retrospective chart reviews were performed, and the degree of scar contracture, pharyngeal stenosis, vocal fold movements, and adverse events were evaluated. Scar contracture was assessed using a scoring system, which compared the endoscopic findings of treatment and matched pair control groups. Results: A total of 20 patients received local steroid injections during TOVS and were enrolled in the treatment. Scar contracture was seen in 14 patients (70%); however, the degree of scar contracture was significantly decreased when compared to control cases. Vocal fold immobility was observed in five patients, but no pharyngeal stenosis was noted. Adverse effects, such as postoperative laryngeal chondritis or cervical spondylitis, were seen in three patients who had previously been treated with resection to the muscularis propria or definitive irradiation. Conclusion: Local steroid injection during TOVS significantly reduced the degree of postoperative scar contracture. However, caution should be used when treating with local steroid injection during TOVS, as this may complicate wound healing in patients who have already received treatment.